2019
DOI: 10.1063/1.5094516
|View full text |Cite
|
Sign up to set email alerts
|

Design, fabrication and testing of CVD diamond detectors with high performance

Abstract: A single crystal diamond (SCD) detector and a polycrystalline diamond (PCD) detector have been designed and fabricated using electronic grade CVD diamond. The fabricated detectors were tested for their dark current and X-ray photocurrent. It was found that the SCD and PCD detectors have superb signal to noise ratios (SNR) under X-ray irradiation from an Ag target with 10kV and 40kV accelerating voltage, 2000 and 7000 respectively for the SCD detector and 550 and 2000 for the PCD detector. The performance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…It is to be noted that the leakage current density is nearly symmetrical in both directions of the applied electric field, thus reconciling the dominance of bulk conduction over other conduction mechanisms leading to nearly ohmic nature of the deposited contacts. The leakage current density of the SC-diamond detector is consistent with the studies carried out by Liu et al [22] and Tsubota et al [23]. The 𝐶-𝑉 characteristics for ±30 V for the SC-diamond detector is reported by the same authors elsewhere [19].…”
Section: Leakage Currentsupporting
confidence: 89%
See 1 more Smart Citation
“…It is to be noted that the leakage current density is nearly symmetrical in both directions of the applied electric field, thus reconciling the dominance of bulk conduction over other conduction mechanisms leading to nearly ohmic nature of the deposited contacts. The leakage current density of the SC-diamond detector is consistent with the studies carried out by Liu et al [22] and Tsubota et al [23]. The 𝐶-𝑉 characteristics for ±30 V for the SC-diamond detector is reported by the same authors elsewhere [19].…”
Section: Leakage Currentsupporting
confidence: 89%
“…In summary, although HPSI-SiC has the high resistivity required for radiation detection, the charge collection properties and hence the spectral resolution of HPSI SiC detectors of equivalent thickness is poor compared to the diamond detectors. In addition to lower 𝜇𝜏 product and CCE, The time-stability of SC-diamond detectors under constant alpha irradiation is an important issue owing to their prolonged use in tokamaks [22]. One of the advantages of SC-diamond over other semiconductor radiation detectors viz.…”
Section: Alpha Particle Spectroscopy and Irradiation Effectsmentioning
confidence: 99%
“…202 The rough surface of PCD poses challenges in achieving high-resolution contacts, and the relatively high concentration of GBs can restrict carrier transport, affecting the detector performance. Liu et al 195 found that reducing the electrode spacing to a size comparable to the grain size improves the detector performance by mitigating the GB effect. According to the published results, the photoelectrical properties of small-grain CVD diamond are controlled by the amorphous-carbon-lie density of states existed at the GBs.…”
Section: Grain/twin Boundariesmentioning
confidence: 99%
“…(E) Dark current and photocurrent of the SCD and PCD detectors. Reproduced under the terms of the CC‐BY license: Copyright 2019, Authors, published by AIP Publishing 195 …”
Section: Influence Of Microstructures On the Electronic Applications ...mentioning
confidence: 99%
“…Due to its physical and chemical properties, diamond is considered an excellent material for the detection of high-energy photons, ranging from deep-UV to X- and gamma rays. Several groups worldwide developed diamond X-ray detectors and dosimeters, both on single crystals and on polycrystalline diamond [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Diamond detectors have been used to quantify the radiation dose in external beam radiation therapy using X-rays and particle beams [ 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%